2021
DOI: 10.1039/d1ob01898a
|View full text |Cite
|
Sign up to set email alerts
|

Streptomyces aureorectus DSM 41692 and Streptomyces virens DSM 41465 are producers of the antibiotic nucleocidin and 4′-fluoroadenosine is identified as a co-product

Abstract: Genome homologies led to the identification of Streptomyces aureorectus DSM 41692 and Streptomyces virens DSM 41465 as producers of the antibiotic nucleocidin, and also 4’-fluoroadenosine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 24 publications
2
14
0
Order By: Relevance
“…A distinct clade is formed by S. calvus ATCC 13382, S. calvus NR_041122, S. virens NR_043842, S. asterosporus NR_041193, and S. aureorectus NR_041195, with the 16S rRNA sequences having 99 % or greater identity. An analogous phylogenetic relationship was reported by Chen and co‐workers [34] . Whole genome sequencing followed by AntiSMASH analysis revealed that S. virens and S. aureorectus contain 35 and 37 predicted BGCs, respectively (Tables S1, S2).…”
Section: Resultssupporting
confidence: 81%
See 4 more Smart Citations
“…A distinct clade is formed by S. calvus ATCC 13382, S. calvus NR_041122, S. virens NR_043842, S. asterosporus NR_041193, and S. aureorectus NR_041195, with the 16S rRNA sequences having 99 % or greater identity. An analogous phylogenetic relationship was reported by Chen and co‐workers [34] . Whole genome sequencing followed by AntiSMASH analysis revealed that S. virens and S. aureorectus contain 35 and 37 predicted BGCs, respectively (Tables S1, S2).…”
Section: Resultssupporting
confidence: 81%
“… [18] The S. virens and S. aureorectus samples revealed 19 F{ 1 H} NMR signals consistent with the known fluoronucleosides 1 (δ=−121.0 ppm), 5 (−119.2 ppm), and 6 (−121.5 ppm). Chen and co‐workers observed production of these compounds along with low levels of 4 in S. virens [34] …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations